Theoretical and Experimental Studies of N,N-Dimethyl-N′-Picryl-4,4′-Stilbenediamine - Papper, Vladislav (2017)
N,N-dimethyl-N′-picryl-4,4′-stilbenediamine (DMPSDA) was prepared, purified and crystallised in a form of black lustrous crystals, and its absorption and fluorescence spectra were recorded in cyclohexane, acetonitrile and dimethyl sulfoxide. Non-emissive intramolecular charge transfer state (ICT) was clearly observed in this molecule in all three solvents. Theoretical calculations demonstrating a betaine electronic structure of the trinitrophenyl group in the ground state of the molecule and a charge transfer nature of the long wavelength transition S0 → S1 supported the experimental observations of the ICT formation in the molecule.